Kajian Yuridis Hak Asasi Manusia terhadap Tindak Pidana Cyberbullying - Kadek Abdi Ramanda Putra (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
Along with the development of the era, the virtual world or the internet is also growing rapidly. In its development, there must be positive and negative things. The term cyberbullying is the use of technology to intimidate, intimidate, or victimize a person or group and this is one of the negative things from the development of the virtual world or the internet. This study uses a normative legal research method, which examines related issues from a human rights perspective and uses laws and regulations and doctrines as study materials for cases that will be classified as cybercrime/stalking or commonly referred to as cyber harassment. Cyberbullying has various forms and approaches. When viewed from a human rights perspective, cyberbullying is strictly prohibited from being carried out on fellow cyberspace users, which in human rights is regulated in Article 30 of Law No. 39 of 1999 concerning Human Rights which reads: "everyone has the right to a sense of comfort and peace and protection against the threat of fear to do or not do something". In this article it is clearly stated that everyone has the right to obtain a sense of comfort in their lives and peaceful conditions and protection from the threat of fear, which refers to cyberbullying which can share the threat of fear against one person and another.